2023
DOI: 10.2174/1573396318666220429085231
|View full text |Cite
|
Sign up to set email alerts
|

Acanthosis Nigricans: An Updated Review

Abstract: Background: Early recognition of acanthosis nigricans is important because acanthosis nigricans can be a cutaneous manifestation of a variety of systemic disorders and, rarely, as a sign of internal malignancy. Objective: This purpose of this article is to familiarize pediatricians with the clinical manifestations, evaluation, diagnosis, and management of acanthosis nigricans. Methods: A search was conducted in November 2021 in PubMed Clinical Queries using the key term "acanthosis nigricans". The search s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 188 publications
0
4
0
1
Order By: Relevance
“…However, no literature report has shown that Testo levels are crucial to bariatric surgery-induced OB_AN remission. A common mechanism for the development of OB_AN is insulin resistance 31 , and Hammarstedt et al . 32 have found that Testo plays a key role in regulating insulin resistance, so we combined the literature and our results to suggest that the remission mechanism after OB_AN surgery could be that Testo affects insulin and contributes to the improvement of OB_AN pathologies by affecting insulin.…”
Section: Discussionmentioning
confidence: 99%
“…However, no literature report has shown that Testo levels are crucial to bariatric surgery-induced OB_AN remission. A common mechanism for the development of OB_AN is insulin resistance 31 , and Hammarstedt et al . 32 have found that Testo plays a key role in regulating insulin resistance, so we combined the literature and our results to suggest that the remission mechanism after OB_AN surgery could be that Testo affects insulin and contributes to the improvement of OB_AN pathologies by affecting insulin.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of post-streptococcal diseases is based on clinical history and findings compatible with the specific illness associated with the evidence of a preceding group A strep infection, including the isolation of GAS from the throat/skin or the detection of certain streptococcal antibodies (anti-streptolysin O and anti-DNase B). A four-fold increase in titer is considered the proof of antecedent streptococcal infection [27,29,33,[42][43][44].…”
Section: Diagnosis Of Gas Infectionsmentioning
confidence: 99%
“…Finally, the third group, which includes guidelines from Australia and New Zealand, identifies two groups of patients at higher risk: patients of Maori or Aboriginal ethnicity, especially people living in rural areas, characterized by overcrowding and low socioeconomic status, and those with a previous history of acute rheumatic fever aged 3-40 years old. Once a diagnosis of GAS pharyngitis is confirmed, antimicrobial therapy should be promptly initiated to prevent both suppurative and non-suppurative complications, in particular, ARF, in which case the treatment should be initiated within 9 days of symptom onset [44,45].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Acadêmica de Medicina Pontifícia Universidade Católica de Minas Gerais -PUC Betim 4 Médica Faculdade Dinâmica do Vale do Piranga (FADIP). 5 Acadêmica de medicina Universidade do Grande Rio / Unigranrio.…”
unclassified